Comparative Review of Jarimah Khalwat and Ikhtilath: An Analysis of Uqubat in Qanun No. 4 of 2014 and the Indonesian Criminal Code - Muniruddin Ritonga; Mhd Yadi Harahap (Jurnal Cendikia ISNU SU, 2025)
The regulation of jarimah khalwat and ikhtilath is part of Islamic criminal law efforts in maintaining the morality and honor of the community. Both acts are seen as acts that pave the way to more serious moral violations that require preventive legal arrangements. The existence of Qanun No. 4 of 2014 concerning Jinayat in Aceh presents a model of formalization of Islamic criminal law in the plural Indonesian national legal system, while the Criminal Code regulates morality in general without explicitly recognizing the concepts of khalwat and ikhtilath. This study aims to analyze comparatively the regulation and uqubat jarimah khalwat and ikhtilath in Qanun Jinayat and compare it with the regulation of morality in the Indonesian Criminal Code. The research method used is normative legal research with a statutory and conceptual approach, using primary legal materials in the form of Qanun No. 4 of 2014 concerning Jinayat and the Criminal Code, as well as secondary legal materials in the form of Islamic criminal law literature and national criminal law. The results of the discussion show that Islamic criminal law places khalwat and ikhtilath as jarimah ta'zir which is oriented towards the prevention and moral protection of the community, while Qanun Jinayat formulates both acts expressly with proportional and flexible uqubat. The Criminal Code has a different approach by emphasizing concrete consequences and the protection of individual freedoms. This paradigm difference reflects the pluralism of criminal law in Indonesia and emphasizes that Qanun Jinayat functions as a lex specialis that lives in the social and religious context of the Acehnese people, so harmonization with the Criminal Code needs to be carried out through the recognition of regional specificity and a dialogue of fair values.